HIV care in Central and Eastern Europe: How close are we to the target? - Gokengin, Deniz; Oprea, Cristiana; Begovac, Josip; Horban, Andrzej; Zeka, Arzu Nazlı; Sedlacek, Dalibor; Allabergan, Bayjanov; Almamedova, Esmira A; Balayan, Tatevik; Banhegyi, Denes; Bukovinova, Pavlina; Chkhartishvili, Nikoloz; et al. (International journal of infectious diseases, 2018)
OBJECTIVES: The aim of this survey was to describe the current status of HIV care in the countries of Central and Eastern Europe and to investigate how close the region is to achieving the UNAIDS 2020 target of 90-90-90. METHODS: In 2014, data were collected from 24 Central and Eastern European countries using a 38-item questionnaire. RESULTS: All countries reported mandatory screening of blood and organ donors for HIV. Other groups subjected to targeted screening included people who inject drugs (PWID) (15/24, 62.5%), men who have sex with men (MSM) (14/24, 58.3%), and sex workers (12/24, 50.0%). Only 14 of the 24 countries (58.3%) screened pregnant women. The percentages of late presentation and advanced disease were 40.3% (range 14-80%) and 25.4% (range 9-50%), respectively. There was no difference between countries categorized by income or by region in terms of the percentages of persons presenting late or with advanced disease. The availability of newer antiretroviral drugs (rilpivirine, etravirine, darunavir, maraviroc, raltegravir, dolutegravir) tended to be significantly better with a higher country income status. Ten countries reported initiating antiretroviral therapy (ART) regardless of CD4+ T cell count (41.7%), five countries (20.8%) used the threshold of <500 cells/μl, and nine countries (37.5%) used the threshold of <350cells/μl. Initiation of ART regardless of the CD4+ T cell count was significantly more common among high-income countries than among upper-middle-income and lower-middle-income countries (100% vs. 27.3% and 0%, respectively; p=0.001). Drugs were provided free of charge in all countries and mostly provided by governments. There were significant discrepancies between countries regarding the follow-up of people living with HIV. CONCLUSIONS: There are major disparities in the provision of HIV care among sub-regions in Europe, which should be addressed. More attention in terms of funding, knowledge and experience sharing, and capacity building is required for the resource-limited settings of Central and Eastern Europe. The exact needs should be defined and services scaled up in order to achieve a standard level of care and provide an adequate and sustainable response to the HIV epidemic in this region.
Keywords: HIV infekce; RNA, Viral; 90-90-90n targets; Central Europe; počet CD4 lymfocytů; Evropa; Europe; HIV care; RNA virová; Eastern Europe; lidé; Humans; CD4 Lymphocyte Count; HIV Infections